TEACHING CROSS CULTURAL UNDERSTANDING BY USING FILM TO INCREASE STUDENTS’ CULTURAL AWARENESS - Luli Sari Yustina (International Conference on Languages and Arts, 2015)
The objective of the paper is that how English Language Lecturer can teach about culture because language is embedded in culture and therefore cannot be understood apart from culture. Learning language means learning culture of the language because a language is a part of culture .Cross Cultural Understanding deals explicitly with different aspect of culture, how and why misunderstandings occur and how to negotiate a culture different from one’s own and deals with such misunderstandings. Culture and communication (using language) are inseparable because culture not only dictates who talks to whom, about what, and how the communication proceeds, it also helps to determine how people encode messages, the meanings they have for messages, and the conditions and circumstances under which various messages may or may not be sent, noticed, or interpreted (Samovar, Porter, & Jain, 1981). Culture is a broad concept that embraces all aspects of human life. It includes everything people learn to do. It is everything humans have learned. Culture shapes our thoughts and actions, and often does so with a heavy hand according to Brooks (1975). We should realize that knowing the language, as well as the patterns of everyday life, is a prerequisite to appreciating the fine arts and literature, therefore we need a balanced perspective of culture when designing curricula. As a strategy to help students to understand the process of transferring the message is watching the eastern movies (films). Many examples of using literature and movies (films) can be found to teach about culture. By watching movies is one of quick process for understanding what, why, how, habit, and values etc of others culture was explored.